Women’s Views on Their Diagnosis and Management for Borderline Gestational Diabetes Mellitus - Shanshan Han; Philippa F. Middleton; Tanya K. Bubner; Caroline A. Crowther (Journal of Diabetes Research)
Introduction. Little is known about women’s views relating to a diagnosis of borderline gestational diabetes mellitus (GDM) and the subsequent management. This study aimed to explore women’s experiences after being diagnosed with borderline GDM, their attitudes about treatment, and factors important to them for achieving any lifestyle changes. Methods. We conducted face-to-face, semistructured interviews with women diagnosed with borderline GDM. Results. A total of 22 women were interviewed. After a diagnosis of borderline GDM, 14 (64%) women reported not being concerned or worried. Management of borderline GDM was thought by 21 (95%) women to be very important or important. Eighteen (82%) women planned to improve their diet and/or exercise to manage their borderline GDM. The most frequently mentioned enabler for achieving intended lifestyle change was being more motivated to improve the health of their baby and/or themselves (15 women). The most frequent barrier was tiredness and/or being physically unwell (11 women). Conclusions. A diagnosis of borderline GDM caused some concern to one-third of women interviewed. The majority of women believed managing their borderline GDM was important and they planned to improve their lifestyle. Women’s own and their babies’ future health were powerful motivators for lifestyle change.